(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article discusses the technology of creating digital geodetic maps, their importance in the fields of geodesy and cartography, and the processes of collecting, processing and visualizing spatial data using modern Geographic Information Systems. The study also analyzes geodetic measurement methods, GPS technologies and the capabilities of GIS software. The results show that digital geodetic maps play an important role in territorial management, land resource accounting and the development of cadastral systems.